Rheological properties of local pineapple fruit jam - Mansor, Atikah; Shamsudin, Rosnah; Mat Hashim, Dzulkifly (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The objective of this study is to determine the rheological properties of local pineapple fruit jam at different temperatures of 20, 30, 40, 50 and 60 °C. The experiments were conducted at room temperature using a rheometer as the measuring device. Pineapple fruit jam was chosen because this type of fruit is commonly grown in Malaysia. The jam was prepared at a Brix concentration of 50 %. The rheological properties of the pineapple jam were examined and it was found to exhibit a pseudoplastic behaviour. From the rheological data obtained, it was determined that the Herschel-Bulkey Model was the best fit model and that the Arrehenius equation successfully describes the effect of temperature on the viscosity of pineapple jam.